2018
DOI: 10.1371/journal.ppat.1007440
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation contributes to CD4+ T cell-mediated protective immunity against blood-stage Plasmodium infection

Abstract: CD4+ T cells play predominant roles in protective immunity against blood-stage Plasmodium infection, both for IFN-γ-dependent effector mechanisms and providing B cell helper signals. Neddylation, an ubiquitination-like process triggered by covalent conjugation of NEDD8 to specific targets, has emerged as a potential regulator of T cell activities to TCR engagement. However, its contribution to T cell-mediated immunity to blood-stage malaria remains unclear. Here using an experimental model induced by Plasmodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…Moreover, neddylation inhibition leads to impaired antigen-driven cytokine production (e.g. IFN-γ, IL-2 and IL-4), which is required for efficient Th1 and Th2 differentiation [70], demonstrating a potent positive function of neddylation pathway in T-cell activation [69, 71]. Consistently, deletion of RBX2 significantly decreased T-cell activation and T-effector cytokine release upon in vitro allogeneic stimulation [72].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, neddylation inhibition leads to impaired antigen-driven cytokine production (e.g. IFN-γ, IL-2 and IL-4), which is required for efficient Th1 and Th2 differentiation [70], demonstrating a potent positive function of neddylation pathway in T-cell activation [69, 71]. Consistently, deletion of RBX2 significantly decreased T-cell activation and T-effector cytokine release upon in vitro allogeneic stimulation [72].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, neddylation pathway seems to directly regulate Shc to facilitate the formation of a ZAP70-Shc-Grb2 signaling complex and affect downstream Erk activation [69, 74]. Subsequently, Cheng et al reported that neddylation pathway is required for supporting various aspects of CD4 + T-cell functions, through B cell lymphoma-2 (Bcl-2)-mediated suppression of the mitochondria-dependent apoptosis [71]. Moreover, neddylation contributes to follicular Th cells differentiation, probably via augmenting the activity of ubiquitin ligase activity Itch by a mono-neddylation process and subsequent proteasomal degradation of FOXO1, a transcription factor implicated in multiple aspects of T-cell functions [71, 75].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of protein neddylation in immunological regulation has received increasing attentions (1214). The inhibition of neddylation leads to the suppression of LPS-induced pro-inflammatory cytokine production in macrophage cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that blocking the neddylation pathway suppresses influenza virus replication and the pro-inflammatory response (20). Finally, neddylation enhances CD4 + T cell-mediated protective immunity against–blood stage Plasmodium infection (12). Interestingly, MLN4924, an inhibitor of NAE, inhibits TLR3/4 and retinoic acid-inducible gene I-induced IFN-β expression by preventing IRF3 binding to the IFN-β promoter, with a neddylation-independent manner (21).…”
Section: Introductionmentioning
confidence: 99%